GAMBARAN RISIKO JATUH PADA LANSIA MENGGUNAKAN TIME UP AND GO TEST - Herma Desmillenia Bintari Lijang; Rika Sabri; Siti Yuliharni (LLDIKTI Wilayah X, 2023)
Falling is a problem that often occurs in the elderly as a result of a decrease in body functions associated with the aging process. Falls are also a major cause of morbidity and mortality in the elderly. The purpose of this study was to describe the risk of falling in the elderly using the time up and go test in the working area of ​​the Belimbing Health Center. This research is a quantitative research with a descriptive design and an observational approach. The sampling technique used is a non-probability sampling technique using purposive sampling with a sample size of 360 elderly. The analysis used in this research is univariate analysis. The results of the study showed that most of the elderly (77.2%) were aged 60-74 years, most (66.1%) were female, most (66.9%) suffered from hypertension, most (74.7% ) had no history of falling, most (86.9%) did not use walking aids, a small proportion (13.1%) used a cane when walking, and more than half (53.3%) had a history of high falls. In this study, it was found that more than half of the elderly in the working area of ​​the Belimbing Health Center had a high risk of falling. So it is necessary to do fall risk screening and provide balance training, especially in the elderly with a high risk of falling.